An umbrella meta-analysis of microbial therapy on hepatic steatosis, fibrosis, and liver stiffness in metabolic dysfunction-associated steatotic liver disease - Kurban, Gvzalnur; Chen, Xiangjun; Jin, Xingyi; Xia, Hui; Wang, Shaokang; Sun, Guiju (Frontiers in Nutrition, 2025)
BackgroundMetabolic dysfunction-associated steatotic liver disease is considered the leading cause of chronic liver disease worldwide. By now, no confirmed medication is accessible for the treatment of MASLD. Previous studies showed the positive effects of microbial therapy, such as probiotics, prebiotics, and synbiotics. The study aims to summarize the results of a meta-analysis of randomized controlled trials and evaluate the impact of microbial therapy (probiotics, prebiotics, and synbiotics) on liver radioactive indicators in patients with MASLD and hopes to bring certain benefits to the adjuvant treatment of MASLD populations.MethodsA thorough search of PubMed, Scopus, Web of Science, Embase, and Cochrane Library, from inception up to 4 May 2025, was conducted to find meta-analyses on randomized controlled trials reporting the effects of microbial therapy on patients with MASLD. Meta-analyses surveying the impact of microbial therapy on the degree of liver fat infiltration (DFI), hepatic steatosis (HS), hepatic fibrosis (HF), and liver steatosis measurement (LSM) in the MASLD patients were included in our umbrella review. The final effect size (ES) was estimated, and sensitivity and subgroup analyses were performed to explore heterogeneity.ResultsA total of 14 meta-analysis studies were included. The findings demonstrated that microbial therapy could significantly improve hepatic steatosis (measured by ultrasound grading) (HS; OR: 2.612; 95% CI: 1.674, 4.075; p < 0.001), hepatic fibrosis (HF; ES: -0.274; 95%CI: −0.427, −0.120; p < 0.001), and liver stiffness measurement (LSM; ES: −0.550; 95%CI, −0.716, −0.384; p < 0.001) in patients with MASLD.ConclusionThe present study suggests that microbial therapies seem to be a promising therapeutic approach to the improvement of hepatic steatosis, liver fibrosis, and liver stiffness in patients with MASLD.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251043303, identifier PROSPERO (CRD420251043303).